2024
DOI: 10.3390/foods13020340
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Loquat Jam Quality at Different Cooking Times Based on Physicochemical Parameters, GC-IMS and Intelligent Senses

Mingfeng Qiao,
Huan Xiong,
Xuemei Cai
et al.

Abstract: The study compared and analyzed the quality of loquat jam with different cooking times through physicochemical parameters, headspace-gas chromatography-ion migration spectroscopy (HS-GC-IMS) and intelligent senses. The results showed that with the prolongation of the cooking time, the color of loquat jam slowly deepened, the energy significantly increased, the adhesiveness, gumminess, hardness and chewiness enhanced, the free amino acid content increased from 22.40 to 65.18 mg/g. The organic acid content incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…3 A, B). Oxalic acid, with a low threshold value of 0.504 mg/g, is identified as the primary contributor to the sour taste in radishes due to its high intensity of sour perception ( Qiao et al, 2024 ). As the previous study reported, oxalic acid is the major organic acid in raw radish and maintained one of the highest concentrations even across fermentation ( Gutiérrez & Perez, 2004 ; Y.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 A, B). Oxalic acid, with a low threshold value of 0.504 mg/g, is identified as the primary contributor to the sour taste in radishes due to its high intensity of sour perception ( Qiao et al, 2024 ). As the previous study reported, oxalic acid is the major organic acid in raw radish and maintained one of the highest concentrations even across fermentation ( Gutiérrez & Perez, 2004 ; Y.…”
Section: Resultsmentioning
confidence: 99%
“…Referring to Qiao et al (2024) , The contents of free amino acids (FAAs) were measured as follows: the radish was homogenized (the mass ratio of radish to ultra-pure water was 1:1) using a wall breaker, then 20 g homogenate was added in 10 mL of 7% sulfosalicylic acid, and ultrasonic was carried out at 40 °C for 40 min. The mixture was centrifuged at 12,000 rpm for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…After picking loquat, complex physicochemical changes will occur in the storage process, and preservation methods on its quality characteristics have a great impact. Therefore, appropriate preservation methods can reduce the changes in loquat quality brought about by prolonged storage time [10].…”
Section: Introductionmentioning
confidence: 99%